Magnetic Properties of Nickel Ferrite Magnetic Nanoparticles Prepared via Glycine Assisted Sol-Gel Auto Combustion Route. (October 2020) - Bajaj, S; Patil, P; Kakade, G N; Tapsale, S D; Jadhav, K M; Shinde, S
Abstract: The present research paper deals on the synthesis of nickel ferrite (NiFe2 O4 ) nanoparticles using sol-gel auto combustion technique in which glycine was used a chelating agent. The prepared nanoparticles were annealed at 500°C for 4 h. and then used for structural, magnetic and other investigations. The X-ray diffraction technique was used for phase purity and structural determination. Room temperature X-ray diffraction pattern of NiFe2 O4 nanoparticles shows all the reflections belonging to cubic spinel structure. The reflections are intense and slightly broader. No extra peak other than cubic spinel structure was observed in the XRD pattern. This indicates the single phase formations of the nickel ferrite nanoparticle. The refinement of XRD data has been carried out by using full proof programmer. The lattice constant was calculated using XRD data as well as Cohen's least square method, the obtained lattice constant matches with the reported value. The other structural parameters like lattice strain, X-ray density etc. structural parameters were also calculated using standard relations. The crystallite size was determined using Scherrer's formula in which the most intense peak (311) was considered. The crystallite size was found to be 24 nm which indicates the nanocrystalline nature of the prepared nickel ferrite nanoparticles. The magnetic properties of were investigated using the pulse field hysteresis loop (PFHL) technique at room temperature. The saturation magnetization, coercivity and remanence magnetization shows enhanced values. All the structural and magnetic properties results were compared with the reported data in which other chelating agent like citric acid etc.